2013
DOI: 10.1167/13.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Systematic biases in adult color perception persist despite lifelong information sufficient to calibrate them

Abstract: Learning from visual experience is crucial for perceptual development. One crucial question is when this learning occurs and to what extent it compensates for changes in the visual system throughout life. To address this question, it is essential to compare human performance not only to the hypothetical state of no recalibration, but also to the ideal scenario of optimum learning given the information available from visual exposure. In the adult eye, macular pigment introduces nonhomogeneity in color filtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 77 publications
2
19
0
Order By: Relevance
“…This illustrates a case where modeling specific forms of adaptation can be used to reveal the presence of additional compensatory processes. (The studies of Bompas et al (2013) and O’Neil and Webster (2014) also draw attention to the finding that this compensation is not perfect, yet the residual errors reflect very minor deviations relative to the enormous degree of constancy already afforded by von Kries scaling, which again underestimates the level of constancy observed. )…”
Section: Color Constancy and Compensation For Variations In The Obmentioning
confidence: 94%
See 1 more Smart Citation
“…This illustrates a case where modeling specific forms of adaptation can be used to reveal the presence of additional compensatory processes. (The studies of Bompas et al (2013) and O’Neil and Webster (2014) also draw attention to the finding that this compensation is not perfect, yet the residual errors reflect very minor deviations relative to the enormous degree of constancy already afforded by von Kries scaling, which again underestimates the level of constancy observed. )…”
Section: Color Constancy and Compensation For Variations In The Obmentioning
confidence: 94%
“…Third, color percepts are in fact more stable than predicted by multiplicative gain changes in the receptors, which can discount most but not all of the spectral shifts from an illuminant change or a change in prereceptoral screening pigments (Bompas, Powell & Sumner, 2013, O'Neil & Webster, 2014, Webster, Halen, Meyers, Winkler & Werner, 2010a). This illustrates a case where modeling specific forms of adaptation can be used to reveal the presence of additional compensatory processes.…”
Section: Color Constancy and Compensation For Variations In The Obmentioning
confidence: 99%
“…Perceived focus is largely corrected for the optical aberrations of the eye, but for higher-order aberrations is more effectively adjusted to the magnitude than the specific blur pattern (Sawides et al, 2012). Compensation of color appearance for lens and macular pigment is better than predicted by adapting to the average color alone – suggesting it goes beyond independent gain changes in the cones – but residual errors remain (Bompas et al, 2013, O'Neil and Webster, 2014). An interesting example of the limits of adaptation for color perception is anomalous trichromats.…”
Section: Adaptation and Compensationmentioning
confidence: 97%
“…In the same way, screening the light with a filter like macular pigment could not be compensated only by rescaling the average sensitivity of each cone. The finding that color constancy was actually better than von Kries scaling implies that additional mechanisms contribute to the stability of color appearance across the visual field [11,14] and argues against suggestions from hue cancellation experiments that only some dimensions of color coding are compensated for macular screening [1517]. Candidate cell types that could promote constancy beyond photoreceptor adaptation, such as double-opponent receptive fields, have been considered in a wide variety of studies (e.g., [1822]).…”
Section: Introductionmentioning
confidence: 99%
“…However, Bompas et al [14] subsequently focused on comparing the color appearance of purple and more saturated surfaces, where any effects of macular pigment should be greatest. They also found that color appearance was more stable than would be predicted by average gain changes in the foveal and peripheral cones.…”
Section: Introductionmentioning
confidence: 99%